Combination Superficial Temporal Artery-Middle Cerebral Artery Bypass and M2–M2 Reanastomosis With Trapping of a Stented Distal Middle Cerebral Artery Aneurysm: 3-Dimensional Operative Video. Issue 5 (12th May 2018) - Burkhardt, Jan-Karl; Yousef, Sonia; Tabani, Halima; Benet, Arnau; Rubio, Roberto Rodriguez; Lawton, Michael T
Abstract: Distal middle cerebral artery (MCA) aneurysms often have non-saccular morphology and cannot be clipped, requiring revascularization and trapping instead. Combination bypasses are needed when 2 arteries exit the aneurysm, and extracranial–intracranial and intracranial–intracranial bypasses can be used. This video demonstrates a combination bypass used to treat a previously stented distal MCA aneurysm with both a superficial temporal artery (STA)-to-MCA bypass and an M2-to-M2 reanastomosis. This 56-yr-old man presented with distal left-sided MCA aneurysm 2 years earlier and attempted stent-assisted coiling was aborted after the aneurysm was perforated with stenting alone. Follow-up angiography demonstrated progressive aneurysm enlargement, and he was referred for surgery. The patient consented for the procedure and a pterional craniotomy extended posteriorly exposed the distal Sylvian fissure and efferent M4-cortical arteries. After splitting the Sylvian fissure, the "flash fluorescence" technique with indocyanine green (ICG) videoangiography identified an M4 recipient artery from the deeper of 2 exiting branches for STA–MCA bypass. 1 The aneurysm was then trapped, and inflow and the more superficial outflow arteries were anastomosed end to end (M2–M2 in-situ bypass). A platelet plug that developed at the reanastomosis site was broken apart with mechanical manipulation, and ICG videoangiography demonstrated patency of both bypasses. The patient recovered without any neurological deficits, and postoperative computed tomography angiography confirmed bypass patency. Combination bypasses are needed when unclippable bifurcation aneurysms require revascularization. Careful intraoperative evaluation of patency of the bypass is imperative and helps identifying and addressing any potential early bypass occlusion.